Does stricter immigration policy affect college enrollment and public-private school choice of natives? - Christian Gunadi (IZA Journal of Development and Migration, 2018)
In recent decades, the USA has admitted a large number of foreign-born students into its educational system, raising concerns that the presence of foreign-born students would adversely impact the educational achievement of US-born students and incentivize them to move to private schools where there are fewer immigrant students. In this article, I attempt to extend our understanding of how stricter immigration policy, such as the Legal Arizona Workers Act (LAWA), may affect college enrollment and the public-private school choice of US-born individuals. The analysis shows that the share of immigrant students across Arizona's educational system declined significantly by the passage of LAWA: the share of foreign-born students in elementary and secondary schools in Arizona would be higher by approximately 1.1 and 1.7 percentage points, respectively, in the absence of LAWA. Similarly, the share of foreign-born college students in Arizona declined significantly by 1.5 percentage points due to LAWA. Despite this decline, there is no evidence that LAWA has statistically significantly affected natives' college enrollment rates. However, there is evidence that LAWA reduces the proportion of US-born white non-Hispanic student in higher education attending private colleges.
Keywords: J24; J61; I20; 330; Immigration; Native college enrollment; Public school; Education